Outstanding elastic, electronic, transport and optical properties of a novel layered material C4F2: first-principles study. Issue 38 (1st July 2021) - Vu, Tuan V.; Phuc, Huynh V.; Ahmad, Sohail; Nha, Vo Quang; Van Lanh, Chu; Rai, D. P.; Kartamyshev, A. I.; Pham, Khang D.; Nhan, Le Cong; Hieu, Nguyen N.
Abstract : Motivated by transformation of AB-stacking bilayer graphene into fluorinated single-layer diamond (fluorinated diamane C4 F2 ), we investigate the structural, elastic, electronic, transport, and optical properties of fluorinated diamane C4 F2 using density functional theory. Abstract : Motivated by very recent successful experimental transformation of AB-stacking bilayer graphene into fluorinated single-layer diamond (namely fluorinated diamane C4 F2 ) [P. V. Bakharev, M. Huang, M. Saxena, S. W. Lee, S. H. Joo, S. O. Park, J. Dong, D. C. Camacho-Mojica, S. Jin, Y. Kwon, M. Biswal, F. Ding, S. K. Kwak, Z. Lee and R. S. Ruoff, Nat. Nanotechnol., 2020, 15, 59–66], we systematically investigate the structural, elastic, electronic, transport, and optical properties of fluorinated diamane C4 F2 by using density functional theory. Our obtained results demonstrate that at the ground state, the lattice constant of C4 F2 is 2.56 Å with chemical bonding between the C–C interlayer and intralayer bond lengths of about 1.5 Å which are close to the C–C bonding in the bulk diamond. Based on calculations for the phonon spectrum and ab initio molecular dynamics simulations, the structure of C4 F2 is confirmed to be dynamically and thermally stable. C4 F2 exhibits superior mechanical properties with a very high Young's modulus of 493.19 N m −1 . Upon fluorination, the formation of C–C bonding between graphene layers has resulted in a comprehensive alteration of electronic properties of C4 F2 . C4 F2 is a direct semiconductor with a large band gap and phase transitions are found when a biaxial strain or external electric field is applied. Interestingly, C4 F2 has very high electron mobility, up to 3.03 × 10 3 cm 2 V −1 s −1, much higher than other semiconductor compounds. Our findings not only provide a comprehensive insight into the physical properties of C4 F2 but also open up its applicability in nanoelectromechanical and optoelectronic devices.